Microwave-Assisted Synthesis and Spectral Identification of 1-Butyl-3- methylimidazolium bis(trifluoromethanesulfonyl)imide [Bmim]NTf2 Ionic Liquid - Wang, Ping; Yang, Mingdi; Su, Yongqing; Li, Cong (Asian Journal of Chemistry, 2011)
In this work, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([Bmim]NTf2), a room-temperature ionic liquid, was synthesized by two-step method. Firstly, the ionic liquid intermediate, alkylimidazolium containing bromo anion ([Bmim]Br) was synthesized from 1-methylimidazole (C4H6N2) and 1-butyl bromide under microwave irradiation. Then [Bmim]Br reacted with lithium bis(trifluoromethanesulfony)imide (Li(CF3SO2)2N)to be [Bmim]NTf2. The structure of [Bmim]NTf2 was characterized and analyzed by 1H NMR, infrared spectrum and UV-VIS spectrum